Anthem, for the Wedding of Frederick Prince of Wales, and the Princess of Saxa-Gotha. Composed in the Year 1736. - Handel, George Frideric 1685-1759 (London Arnold)
Frederick, Prince of Wales (1707-1751) son and heir of King George II, married Princess Augusta of Saxe-Gotha-Altenburg (1719-1772) in 1736. He was the eldest son of George II and Queen Caroline and father to the future George III. He spent much of his life at odds with his own father. He was excluded from both the business of ruling and the public eye and thus used art and music to establish himself amongst the aristocracy and court. Today he is remembered as a great lover and patron of music. Frederick spent his early years in Germany and during his education there he became proficient at both the cello and the harpsichord. In 1733 Frederick formed his own opera company called the Opera of the Nobility. Its first principal composer was Nicola Porpora, later the teacher of Haydn. This was a bold move at the time as it was set up to rival the Royal Academy of Music, which was established by Handel and officially patronised by his father, George II. This is not to say, however, that Frederick was antagonistic towards Handel.
Bound in with 'Anthem, for the Funeral of Queen Caroline. Composed in the Year 1737', 'Anthem, for the Victory at Dettingen. Composed in the Year 1743' and '3 Anthems, for the Coronation of George IId. Composed in the year 1727'
Keywords: Frederick -- Prince of Wales -- 1707-1751; 18th Century (1701-1800); Anthem; Wedding; United Kingdom